2015
DOI: 10.3390/foods4020148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Hydrostatic Pressure on Water Absorption of Adzuki Beans

Abstract: The effect of high hydrostatic pressure (HHP) treatment on dried soybean, adzuki bean, and kintoki kidney bean, which are low-moisture-content cellular biological materials, was investigated from the viewpoint of water absorption. The samples were vacuum-packed with distilled water and pressurized at 200 MPa and 25 °C for 10 min. After the HHP treatment, time courses of the moisture contents of the samples were measured, and the dimensionless moisture contents were estimated. Water absorption in the case of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Figure 1a shows that mung bean has sigmoidal behavior during hydration under its normal (equilibrium with environment) initial moisture content (25 °C, 12.25% d.b. ), similarly to other pulses such as Andean lupin4, Adzuki beans32122, Cowpea8 and Italian Lima beans23. Further, its hydration behavior changes to the DCS when the initial moisture is increase.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 1a shows that mung bean has sigmoidal behavior during hydration under its normal (equilibrium with environment) initial moisture content (25 °C, 12.25% d.b. ), similarly to other pulses such as Andean lupin4, Adzuki beans32122, Cowpea8 and Italian Lima beans23. Further, its hydration behavior changes to the DCS when the initial moisture is increase.…”
Section: Resultsmentioning
confidence: 93%
“…The relative water absorption of untreated and scratched KB seeds was similar (Figure ). Ueno and others () suggested that uniform/homogeneous water absorption facilitates bean cooking and increases the demand for such functional foods.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the possible enhancement of the hydration process by high hydrostatic pressures is still uncertain. There are 6 works that have used this technology to date (Sangronis and others ; Ibarz and others ; Ramaswamy and others ; Ueno and others ; Belmiro ), all applied high pressures as a pre‐treatment for chickpeas, adzuki beans, navy beans, carioca beans and black kidney beans. All these works used pressures from 33 MPa to 700 MPa and reported that this technology improved the hydration process by increasing the hydration rate.…”
Section: Hydration Process Improvementmentioning
confidence: 99%